Exploring the relationship and agreement of asymmetry between lateral jump and change of direction in young tennis players - Trecroci, A.; Mantegazza, S.; Formenti, D. (International Journal of Performance Analysis in Sport, 2025)
The main aim of this study was to examine the relationship and the degree of agreement between lateral jump and change of direction (COD) asymmetries favouring the same lower limb in young tennis players. Thirty-one tennis players (U12, U14, and U17) voluntarily participated in the study. They were tested for lateral movement and COD performance by the single-leg lateral jump (SLLJ) and the modified 505 COD test (505mod). The asymmetric index (AI%) of both tests was obtained alongside an asymmetric threshold (AT%) for each age group. The level of agreement between SLLJ and 505mod was assessed by Cohen`s kappa statistic (?). The main finding revealed that the AI% observed in the SLLJ (median: 4.4%, interquartile range: 1.7-6.3) slightly agree (? = -0.148) with that of 505mod (median: 6.3%, interquartile range: 4.6-10.3) alongside with a non-significant (r = 0.105, p > 0.05) association to each other, indicating their imbalance did not favour the same direction. The AT% tended to decrease with age, possibly with the increasing training background. Practitioners should consider the task-specificity of asymmetry to reduce the imbalance in lateral jump and COD performance on the tennis court.